Biodegradation properties of poly (Lactic) acid reinforced by kenaf fibers - Surip, S.N. Surip; Wan Jaafar, W.N.R.; Azmi, N.N.; Hassan, Noor Azlina (POLISH ACAD SCIENCES INST PHYSICS, 2016)
This study was conducted to study the degradation of poly (lactic acid) and its composites under natural landfill burial. Composites reinforced with natural fibres were expected to degrade faster than polymer itself. PLA was compounded with kenaf bast fibre (KBC) and kenaf core fibre (KCC) with twin screw extrusion at temperature range 150-160 degrees C and being compression moulded at 170 degrees C for 8 minutes. Samples were then cut prior to testing by burying under composting area in UiTM Shah Alam, Selangor, Malaysia for 6 month period. Samples were measured and observed monthly for the degradation of composites by weight loss and microscopic observation. As expected weight loss for kenaf bast composite (KBC) and kenaf core composite (KCC) was found to be higher, 15.9% and 17.1% respectively, than that of pure PLA of only 4.14%. Microscopic observation confirms degradation has occurred on surface of composites by making cracks, holes, and black spots on all samples, however degradation was more obvious on composites. FTIR analysis shows that spectra of exposed composites were reduced compared to those of unexposed composites.